METODE GURU DALAM MENGATASI KESULITAN SISWA MEMBACA AL-QURAN PADA PEMBELAJARAN AL-QURAN HADITS DI KELAS II MADRASAH IBTIDAIYAH SWASTA TARBIYAH TEBAS TAHUN PELAJARAN 2024/2025 - Maya; Ubabuddin; Rathomi, Ahmad (Lunggi Journal, 2025)
This research began with the discovery of a case about the teacher's method in overcoming students' difficulties in reading the Qur'an. The purpose of this research is to reveal: (1) Students' difficulties in reading the Qur'an in the Qur'an Hadith learning of class II at MIS Tarbiyah Tebas in the 2024-2025 academic year. (2) Teachers' methods in teaching students to read the Qur'an in the Qur'an Hadith learning of class II at MIS Tarbiyah Tebas in the 2024-2025 academic year. (3) Teachers' solutions in overcoming students' difficulties in reading the Qur'an in the Qur'an Hadith learning of class II at MIS Tarbiyah Tebas in the 2024-2025 academic year. This research uses a qualitative approach with a case study research type. Data collection techniques use observation, interviews and documentation. Data analysis techniques are carried out by data collection, data reduction, data presentation, and drawing conclusions. Data validity checking techniques use source triangulation, and member checks. The results of the study indicate that: (1) The difficulties experienced by second-grade students of MIS Tarbiyah Tebas in reading the Qur'an include difficulties in identifying letters, pronouncing letters according to the makharijul huruf, reading according to the rules of tajwid, and distinguishing long and short harakat. (2) The method used by the Al-Qur'an Hadith subject teacher to overcome students who experience difficulties in reading the Qur'an is the Iqra' method. (3) The teacher's solution to overcome students' difficulties in reading the Qur'an in learning Al-Qur'an Hadith in second-grade students of MIS Tarbiyah Tebas is providing individual guidance, creating innovative learning, and choosing the right time to study the Qur'an with students. The solutions implemented have been deemed effective in overcoming students who experience difficulties in reading the Qur'an.